Optimasi Green Productivity pada Industri Karet di PT. X Palembang - Rosyidah, Masayu; Sholekah, Lihatus; Oktarini, Devie (Metris: Jurnal Sains dan Teknologi, 2020)
PT. X is a company that processes semi-finished rubber. In its management, the company relies on a number of suppliers of raw rubber. In the production process produces liquid waste. The problem in this research is how to increase company productivity and reduce environmental impact. This study aims to determine the level of company productivity, knowing the EPI index (Environmental Performance Indicator). Methods of conducting research through observation and questionnaires. Based on the results of calculations performed, it shows that the company's productivity is quite good with an average value of 202.56%, while the results of the calculation of the total EPI index are positive because the company has made management efforts in accordance with the applicable provision.